Study on the Effect of Proportion of Soya Flour and Corn Flour on Physicochemical Properties of Pork Nuggets - Sutarjo Surjoseputro; Thomas Indarto Putut Suseno; Dorkas Setiowati (Indonesian Association of Food Technologists, 2004)
Pork nuggets are one of restructured meats. Adding soy flour and corn flour as alternatives to replace wheat flour can produce pork nuggets. Soy protein (globulin) could form gel-protein matrix, besides –protein-starch gel matrix. The formation of matrix increased Water Holding Capacity (WHC) and formed cohesive texture of the products. Combination of 4% soy flour and 6% corn flour is the best treatment to produce acceptable pork nuggets.